2022
DOI: 10.1038/s41467-022-34873-7
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 is a predictive biomarker in idiopathic multicentric Castleman disease

Abstract: Idiopathic multicentric Castleman disease (iMCD) is a rare and poorly-understood cytokine storm-driven inflammatory disorder. Interleukin-6 (IL-6) is a known disease driver in some patients, but anti-IL-6 therapy with siltuximab is not effective in all patients, and biomarkers indicating success at an early time point following treatment initiation are lacking. Here we show, by comparison of levels of 1,178 proteins in sera of healthy participants (N = 42), patients with iMCD (N = 88), and with related disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“… 83 Lymph nodes from patients with iMCD-TAFRO showed an increased expression of CXCL13 compared with lymph nodes of patients with iMCD-NOS. 83 A longitudinal analysis of sera samples of the phase 2 trial 68 was not able to identify pretreatment-specific biomarkers of siltuximab response, but identified CXCL13 as the only protein that was significantly different between responders and nonresponders at early and late time points, with a significant difference observed as early as after 8 days of treatment, in both the primary and validation cohorts. 83 The results indicate that a decrease in CXCL13 of 17% or more after starting siltuximab treatment is predictive of a good response to siltuximab.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“… 83 Lymph nodes from patients with iMCD-TAFRO showed an increased expression of CXCL13 compared with lymph nodes of patients with iMCD-NOS. 83 A longitudinal analysis of sera samples of the phase 2 trial 68 was not able to identify pretreatment-specific biomarkers of siltuximab response, but identified CXCL13 as the only protein that was significantly different between responders and nonresponders at early and late time points, with a significant difference observed as early as after 8 days of treatment, in both the primary and validation cohorts. 83 The results indicate that a decrease in CXCL13 of 17% or more after starting siltuximab treatment is predictive of a good response to siltuximab.…”
Section: Resultsmentioning
confidence: 92%
“…Identifying and validating the subgroup with a superior response to siltuximab was considered the first validated predictive algorithm for response to siltuximab in iMCD. The same authors found that serum CXCL13 was higher in iMCD patients compared with healthy controls but did not differ between iMCD‐TAFRO and iMCD‐NOS 83 . CXCL13 showed potential to discriminate from a portion of pathologies with overlapping features as its serum levels were elevated compared with rheumatoid arthritis and HHV‐8‐MCD patients but not for patients with Hodgkin lymphoma 83 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…1,3 Additionally, a recent serum proteomics study identified and validated C-X-C Motif Chemokine Ligand-13 (CXCL13) as a predictive biomarker of response to siltuximab as early as day 8 after siltuximab initiation; however, CXCL13 is not yet widely available for clinical use. 2 Ultimately, these results indicate that IL-6 values should not be measured after siltuximab administration and should not be used to guide treatment decisions.…”
mentioning
confidence: 99%